Fix of Zn species in silicalite‐2 via a facile crystallisation process control route. (17th June 2020) - Yu, Qingjun; Tang, Xiaolong; Yi, Honghong
Abstract : Zinc species were fixed in the silicalite‐2 zeolite by a crystallisation process control method. By controlling the introduction time of Zn during the crystallisation process, the distribution of Zn species in zeolite crystals can be facilely adjusted. Particularly, as Zn species were introduced after the completion of nucleation or crystal growth, crystals with structure of silica–core and Zn–silica shell will be formed. The ratio of shell to core thickness can be easily varied by adjusting the Zn feeding time as well as controlling the recrystallisation period.